Diabetic encephalopathy: metabolic reprogramming as a potential driver of accelerated brain aging and cognitive decline - Huai, Jia-xuan; Chang, E-e; Zhu, Yi-ran; Ma, Wen-ling; Lv, Tian-su; Sun, Jing; Zhou, Xi-qiao (Frontiers in Cell and Developmental Biology, 2025)
Diabetic encephalopathy (DE) is a serious neurological complication of diabetes and is expressed as progressive decline in cognitive function, emotional disorders, and changes in brain structure. This review brings together the relevant evidence and demonstrates that metabolic reprogramming, the adaptive reconfiguration of the core metabolic pathway in response to hyperglycemia, is a potential driver of accelerated brain aging in DE. The main pathological characteristics are: abnormal brain insulin signaling, resulting in a decrease in neuronal glucose intake and a decrease in mitochondrial oxidative phosphorylation, oxidative stress and neuroinflammation caused by high blood sugar, in which excess reactive oxygen species (ROS), impairs mitochondrial integrity and leads to activation of microglia cells. The impaired mitophagy and the macrophages remove defects and cause the accumulation and energy collapse of the dysfunctional organelles. In addition, it promotes excessive glycolytic flux, lipolysis disorder, lactic acid accumulation, and ceramide-dependent synaptic damage. We further examine shared metabolic mechanisms between DE and neurodegenerative diseases such as alzheimer’s disease (AD) and treatment strategies for pathological metabolic reprogramming including GLP-1 receptor agonists, NAD+ boosters, and AMPK activators. This analysis laid the foundation for new intervention measures against the development of DE.